MESOZOIC GRANITIC MAGMATISM IN EXTENSIONAL TECTONICS NEAR THE MONGOLIAN BORDER IN CHINA AND ITS IMPLICATIONS FOR CRUSTAL GROWTH - Wang T.; Zheng Y.; Li T.; Gao Y. (My University, 2004)
The Yagan area of the southernmost Sino–Mongolian border is characterized by an extensional structure where a large metamorphic core complex (Yagan–Onch Hayrhan) and voluminous granitoids are exposed. New isotopic age data indicate that the granitoids, which were previously regarded as Paleozoic in age, were emplaced in early and late Mesozoic times. The early Mesozoic granitoids have 228±7 Ma U–Pb zircon age, and consist of linear mylonitic quartz monzonites and biotite monzogranites. Their chemical compositions are similar to those of potassic granites and shoshonitic series, and show an intraplate and post-collisional environment in tectonic discrimination diagrams. Their fabrics reveal that they experienced syn-emplacement extensional deformation. All these characteristics suggest that the adjustment, thinning and extensional deformation at middle to lower crustal levels might have occurred in the early Mesozoic. The late Mesozoic granitoids have a U–Pb zircon age of 135±2 Ma, and are made up of large elliptical granitic plutons. They are high-K calc-alkaline, and were forcefully emplaced in the dome extensional setting. Both the early and late Mesozoic granitoids have εNd (t) values of −2.3 to +5, in strong contrast with the negative εNd (t) values (−11) of the Precambrian host rocks. This suggests that juvenile mantle-derived components were involved in the formation of the granitoids. The similar situation is omnipresent in Central Asia. This study demonstrates that tectonic extension, magmatism and crustal growth are closely related, and that post-collisional and intraplate magmatism was probably a significant process for continental growth in the Phanerozoic.
Keywords: Metamorphic core complex; Granitoids; High potassic; U–Pd dating; Central Asian Orogenic Bel; Mesozoic; Мезозой